Aligning financial supervisory structures with country needs - Carmichael, Jeffrey; Fleming, Alexander; Llewellyn, David T.; World Bank Institute (Washington, D.C. : World Bank Institute, 2004)
"Aligning Financial Supervisory Structures with Country Needs" examines experiences from a variety of supervisors and policymakers from different countries to cross-fertilize ideas on issues of financial supervisory structure and to better understand why and how some countries have initiated structural changes. This timely book also identifies the pros and cons of different financial supervisory models.
Papers presented at a conference entitled Aligning financial supervisory structure with country needs on Dec. 4-5, 2003 at the World Bank Institute in Washington, D.C.
Includes bibliographical references.
rpm 16/09/2016
Loans
Keywords: International finance; Monetary policy; Banks and banking, Central